Évolution du sentiment d’auto-efficacité parentale scolaire lors de la transition au secondaire : prédicteurs et relations avec l’adaptation scolaire de l’élève - Perrier, Laurence; Bouffard, Thérèse; Bonneville-Roussy, Arielle (Canadian Journal of Education/Revue canadienne de l'éducation, 2025)
Studies have shown that parental academic self-efficacy, or the parent’s perception of their ability to support their child’s academic motivation and success has been linked to better student adjustment. This longitudinal study examines (1) the trajectories of this feeling among 618 parents over the four years encompassing their child’s transition to secondary school; (2) whether the student’s gender and mental abilities, the parents’ level of education, and their perception of their child’s academic motivation in Grade 5 predict trajectory membership; and (3) whether trajectory membership is related to the student’s academic adjustment in the second year of secondary school. Two relatively stable trajectories emerged: one where parents have a high sense of academic self-efficacy that decreases from the end of primary school onwards, and one where parents initially have a moderate feeling of self-efficacy that decreases slightly over the next three years. Parents’ perception of their child’s academic motivation positively predicted membership in the high trajectory. Students of parents in this trajectory have higher perception of competence, motivation, and academic performance in the second year of secondary school compared to other students.